MONITORING DAN EVALUASI PENERAPAN TEKNOLOGI MODIFIKASI CUACA DI DAS WADUK KASKADE - CITARUM, JAWA BARAT - Akrom, Isnan Fauzan; Fauzi, Muhammad (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
The 2020 drought led to a reduction in the water supply of the Citarum cascade reservoirs (Saguling, Cirata, and Juanda) due the lowering intensity of rainfall in the catchments of the three reservoirs. Rainfall in late 2020 through February 2021 was much lower than the predicted and historical averages. This caused the water level of the Citarum cascade reservoirs fell to be below normal at the end of December 2020. To meet the water demand, an increase in inflow enhancement is needed, hence the implementation of Weather Modification Technology (WMT) which was carried out on March 12th - April 21st, 2021 in the Citarum watershed, West Java Province. WMT is applied for increasing or decreasing the amount of rainfall by intervening in the cloud growth process, which is carried out by seeding NaCl powder on clouds using an airplane. The purpose of monitoring and evaluation (M&E) of WMT implementation is to collect data, analyze, and evaluate the hydrological conditions of the Citarum cascade reservoirs during WMT implementation. The purpose of M&E is to assess the success of additional reservoir volume due to rainfall during WMT implementation. The M&E is conducted by collecting daily data of the rainfall, water level, and hydrological data of the reservoirs. The data collected each day is used as the basis for the seeding strategy on that day. After the WMT implementation activities are completed, an evaluation of the overall WMT implementation results is continued, which includes analyzing rainfall data, river water level, as well as the inflow, volume, and water level of the reservoir. The results of this study show that WMT implementation could not raise the water level of the three reservoirs to the Normal Operating Limit, but it has succeeded in increasing the reservoir volume by approximately 270 million m3 for Saguling, 201 million m3 for Cirata, and 59 million m3 for Juanda.Keywords: Reservoir, Citarum, Weather, Modification, Technology